Association between rivaroxaban use and length of hospital stay, treatment costs and early outcomes in patients with pulmonary embolism: a systematic review of real-world studies. (2nd September 2017) - Kohn, Christine G.; Fermann, Gregory J.; Peacock, W. Frank; Wells, Phil S.; Baugh, Christopher W.; Ashton, Veronica; Crivera, Concetta; Schein, Jeff R.; Wildgoose, Peter; Coleman, Craig I.
Abstract: Background: In the EINSTEIN-Pulmonary Embolism (PE) trial, subjects randomized to rivaroxaban versus enoxaparin bridging to vitamin K antagonist (VKA) therapy experienced a reduced index hospital length of stay (LOS). We sought to conduct a systematic review of real-world studies comparing LOS, costs and early outcomes among patients treated with rivaroxaban or parenterally bridged VKA in routine practice. Methods: We searched Medline and Scopus from 1 January 2011 to 30 November 2016 to identify observational studies comparing acute PE patients anticoagulated with rivaroxaban or parenterally bridged VKA and reporting data on index hospital LOS, costs and/or early post-PE outcomes. Studies not using appropriate methods for minimizing confounding bias or not published in English were excluded. Results: Five studies met inclusion criteria. Rivaroxaban use was associated with decreased index hospital LOS (range: 1.36–1.70 days) and treatment costs (range: $1818–$2688) during an index stay compared to parenterally bridged warfarin. No differences in early readmission for recurrent thrombosis were noted between anticoagulation strategies. Readmission for major bleeding was rare in both cohorts. Similar reductions in LOS (range: 0.23–4.3 days) and costs (range: $251–$7094) were observed with rivaroxaban in studies restricted to patients deemed low risk for early complications by clinical gestalt or by a clinical- or claims-based risk stratification tool. Conclusions: Regardless of patient predicted risk of post-PE complications, real-world studies suggest that rivaroxaban is associated with a reduced hospital LOS and costs versus parenterally bridged warfarin, without increasing readmission.